The effectiveness of educational program based on health belief model on promotion of puberty health concepts among teen girls: a cross-sectional study in north of Iran - Sedighe Bab Eghbal; Zahra Aghaei Kenari; Asieh Ashouri; Nooshin Rouhani-Tonekaboni; Parisa Kasmaei; Fardin Mehrabian; Mahmood Karimy; Fatemeh Rezaei; Esmaeil Fattahi (BMC, 2023)
Abstract Background Puberty is a sensitive critical stage of human life. As numerous healthy habits and behaviors are created during adolescence, correct health education during puberty is essential to maintain and improve an individual's physical, emotional, and mental health. The present study aimed to determine the impact of educational intervention based on the predictors of the Health Belief Model (HBM) on female nine-grade students' health behaviors in Rasht, Iran. Methods The present randomized controlled trial study examined 110 female nine-grade students. Multi-stage sampling was performed, and the students were randomly divided into two groups of 55 as intervention and control. The data collection tool included a valid and reliable questionnaire with four sections, namely demographic variables, knowledge, HBM constructs, and health behaviors during puberty. The educational program comprised four 45-60-min sessions per group (4 groups of 13) based on HBM. The data were collected two times, before and 1 month after the educational intervention, and were analyzed using the independent t-test, paired t-test, chi-square test, and SPSS 23. Results The mean age of menarche was 12.26 ± 1.133 in the intervention group and 12.12 ± 1.263 in the control group. The family was a source of information for students and the main cue to action before the intervention. Before the educational intervention, there was no significant difference between the experimental and control groups in terms of knowledge, HBM constructs, and puberty health behaviors; however, the variables increased significantly in the intervention group after educational intervention (P<0.001). Conclusions Given the effectiveness of the HBM in improving the health behavior of adolescent girls, it is recommended that health policymakers should plan and implement educational interventions in this field.